Bimetallic metal–organic frameworks and MOF-derived composites: Recent progress on electro- and photoelectrocatalytic applications - Zhou, Yingtang; Abazari, Reza; Chen, Jing; Tahir, Muhammad; Kumar, Anuj; Ikreedeegh, Riyadh Ramadhan; Rani, Ekta; Singh, Harishchandra; Kirillov, Alexander M. (Coordination chemistry reviews, 2022)
[Display omitted] •The advantages of BMOFs and their composites are summarized and discussed.•BMOFs and their composites exhibit high electro/photoelectrocatalytic properties.•We investigated the current problems and future solutions of BMOFs.•The challenges of BMOFs for electro/photoelectrocatalysts are summarized.•This is the first review dedicated to BMOFs for electro/photoelectrocatalysts. Owing to the growing demand in areas such as energy, environmental science, electro- and photoelectrocatalysis, different reactions such as HER (hydrogen evolution), OER (oxygen evolution), ORR (oxygen reduction), and CO2RR (CO2 reduction) represent attractive strategies to overcome the challenges in sustainable energy conversion and usage. The competition for introducing catalysts with higher performance and cost-efficiency in comparison to the previous systems based on noble metals is one of the most interesting directions in this field. By merging the advantages of inorganic and organic materials, MOFs (metal–organic frameworks) have gained an ample attention as highly versatile electro- and photoelectrocatalytic platforms. This is governed by the intricate features of MOFs including extraordinary surface area, exceptional porosity, tailorable pore size, vast structural and chemical tunability, and pre- and post-synthesis structural modifiability. In contrast to monometallic compounds, bimetallic MOFs (BMOFs) and their composites offer many advantages, including improved electrical conductivity, extended active sites, high charge capacity, and adjustable electrochemical activity. Metal-organic frameworks can also be combined with other electrochemically active materials, resulting in advanced composites with large specific area, increased electrical conductivity, and superiour dispersion. Besides, some BMOFs show an enhanced electrocatalytic activity under light irradiation, thus permitting their application as photoelectrocatalysts. The present review summarizes the state-of-the-art on bimetallic MOFs and derived composites for the main current types of electro- and photoelectrocatalytic applications. The study also aims to highlight the challenges and opportunities in this area, with a focus on future perspectives of such multimetallic compounds and materials, with a particular emphasis in the field of energy and electrophotocatalysis.